TANTANGAN DAN PROSPEK PELAPORAN KEUANGAN SYARIAH DALAM MENINGKATKAN KEPERCAYAAN INVESTOR - hasran, Katini; Yashari Soumena, Fadly (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to analyze the challenges and prospects of Islamic financial reporting in enhancing investor confidence. Islamic financial reporting not only conveys financial information but also reflects adherence to Islamic principles such as justice, transparency, and social responsibility. This research uses a qualitative approach with a descriptive method through a literature review of financial reports, Islamic accounting standards, and relevant regulatory frameworks. The findings indicate that the main challenges in Islamic financial reporting include low financial literacy, lack of standardized reporting practices, limited human resources, and insufficient digital innovation. On the other hand, the prospects for Islamic financial reporting are promising, particularly with the support of information technology, digitalization, and integration with sustainability reporting. High-quality, transparent, and accountable reporting is proven to increase investor trust in Islamic financial institutions. Therefore, collaboration between regulators, industry, and academia is essential to promote adaptive, reliable, and Sharia-compliant reporting reforms.